An Uncommon Cause of Shortness of Breath in a Young Puerpera - Suartcha Prueksaritanond; Alaa M. Ali; Godson Nnamdi Aronu; Nasir Hussain; Anubha Ganjoo; Aibek E. Mirrakhimov; Aram Barbaryan (Hindawi Limited, 2013)
Acute postpartum dyspnea in a young, previously healthy adult encompasses numerous conditions. One should be aware of various differential diagnoses including delayed postpartum preeclampsia-induced pulmonary edema where the occurrence is rare but a significant one due its deleterious consequences. We report a case of 26-year-old gravida 1/para 1 female who presented to the hospital with progressive dyspnea after 1 week of normal spontaneous vaginal delivery. On physical examination, her blood pressure was severely elevated. Her clinical signs and symptoms were consistent with pulmonary edema, but diagnostic tests excluded the cardiogenic causes. Further test revealed proteinuria. The patient was diagnosed with delayed postpartum preeclampsia.